Endovascular abdominal aortic aneurysm repair in a patient with homozygous sickle cell disease. Issue 1 (25th April 2017) - Dodwell, Richard; Rogers, Simon; Simcox, David; Smout, Jonathan; Fisher, Robert
Summary: As life expectancy of sickle cell disease improves, it can be expected that these individuals will increasingly require complex vascular surgery. We present the first reported case of endovascular repair of an abdominal aortic aneurysm in this patient group. Our patient, despite being aware of the lack of published clinical experience in such cases, strongly favoured definitive repair of his 6.3cm aneurysm. Careful consideration of the surgical options, in consultation with haematologists and anaesthesia personnel, concluded that an endovascular approach was likely to offer the lowest risk of an acute sickling crisis. The multidisciplinary team agreed an individualised perioperative care plan, which included arrangements for prior patient education, pre‐operative exchange transfusion, haemoglobin profile targets, strategies for minimising sickling precipitants and appropriate postoperative care. This collaborative approach, which we believe to be mandatory in such cases, resulted in an uneventful procedure, smooth recovery and a satisfied patient who has returned to normal activities.